Review of Polymer-Grafted Carbon Nanotubes: Synthesis, Properties, and Applications (International Journal of Food and Nutritional Sciences, 2022)
This review examines the synthesis, properties, and diverse applications of polymer-graftedcarbon nanotubes (CNTs). Polymer grafting onto CNTs represents a significant advancementin nanomaterial science, enhancing the functional versatility and applicability of CNTs invarious fields. The synthesis methods discussed encompass both covalent and non-covalentapproaches, highlighting their respective advantages in achieving tailored polymer-CNThybrids with controlled structures and properties. The properties of polymer-grafted CNTs,including mechanical strength, electrical conductivity, and thermal stability, are criticallyanalyzed in the context of their application potential. The synergistic combination of CNTs'intrinsic properties with the functional attributes imparted by polymers broadens their utility infields such as nanocomposites, sensors, biomedical devices, and energy storage systems. Keyapplications reviewed include the use of polymer-grafted CNTs in enhancing mechanicalproperties and electrical conductivity of composites, improving sensitivity and selectivity insensor devices, enabling controlled drug delivery in biomedical applications, and enhancingperformance in energy storage devices. this review underscores the transformative impact ofpolymer grafting on CNTs, offering insights into current advancements, challenges, and futuredirections in utilizing these hybrid materials across various technological domains.